Complex network to enhance characterization analysis in modelling product development process - Bencherif, Fateh; Leila-Hayet Mouss (African Journal of Science, Technology, Innovation and Development, 2020)
Nowadays, successful and innovative product development is highly correlated with the company's success and reason for existence. A development process is a major factor influencing cost, timing and quality of product development. It requires additional attention to decisions made about programme, budget, technical and market risks. In this paper a product development process model is proposed in an innovation context and strategy framework of design process and project management. The process modelling is complex network theory based, to improve characterization analysis for product development process modelling. Required concepts for complex process are established to build product development mathematical model, and provide an overview of key definitions and complex networks advanced tools. Finally, a case study for an Algerian electric generator company is carried out to prove the practicality of the proposed model.